Reducing carbon mineralization and enhancing carbon storage in coastal earth aquaculture pond sediment using Spartina alterniflora-derived biochar - Ping Yang; Junwei Wang; Yongxin Lin; Hong Yang; Wenjing Liu; Qian Zhu; Chuan Tong; Dongyao Sun; Linhai Zhang; Kam W. Tang (Agriculture, Ecosystems & Environment, 2026)

A Lactobacillus plantarum vaccine candidate with dendritic cell targeting and lysosome escape properities provides efficient protection against necrotic enteritis in broiler chickens - Yupeng Gao; Mingyue Wang; Yijie Wang; Yuxi Zhang; Qiyu Guo; Tianrui Yang; Yan Sun; Yuhang Zhang; Xin Wen; Xin Lu; Yao Xu; Tong Wang; et al. (Veterinary Microbiology, 2026)

Corrigendum to ‘Aeolian processes and their dynamics in the desert-loess transition zone of northwestern China since 20 ka: A synthesis of paleoenvironmental records’ [Quat. Sci. Rev. 382(2026) 109957] - Bing Liu; Hui Zhao; Yujie Xu; Aijun Sun; Jianhui Ge; Linhai Yang; Jun Peng; Zhengcai Zhang; Qinghe Niu; Xiaolei Liang (Quaternary Science Reviews, 2026)

Aeolian processes and their dynamics in the desert-loess transition zone of northwestern China since 20 ka: A synthesis of paleoenvironmental records - Bing Liu; Hui Zhao; Yujie Xu; Aijun Sun; Jianhui Ge; Linhai Yang; Jun Peng; Zhengcai Zhang; Qinghe Niu; Xiaolei Liang (Quaternary Science Reviews, 2026)

A new paradigm for electrical modeling in site leakage diagnostics: A label-scarce three-dimensional simulation surrogate using physics-informed neural networks - Feng Chen; Aixia Zhou; Linhai Ye; Wenchang Li; Xiaochen Sun; Jie Zhang; Youcai Zhao; Qifei Huang; Ya Xu (Water Research, 2026)

The Enhancing ‘Heat Dome’ Effect Is Reinforcing the Sustained Surface Summer O 3 Pollution in North China - Hui Gao; Ting Ding; Tiejun Xie; Linhai Sun; Wenjing Li (International Journal of Climatology, 2025)
The air pollution transmission channel in North China, also termed the ‘2 + 26’ cities, has the most severe pollution problem in China. Based on the meteorological and environmental observation data from 2014 to 2022, the spatial–temporal features of the air quality index (AQI) in the ‘2 + 26’ cities are first compared to reveal the different changes in winter and summer. Since the issue of the Air Pollution Prevention and Control Action Plan in China in 2013, the winter AQI averaged at the ‘2 + 26’ cities shows a significant decreasing trend of −9.725 μg m −3 per year from 2014 to 2022, but it shows much slight variation in summer. In summer, the ozone (O 3 ) pollutant is the major contributor to the AQI. Results indicate that higher T max and lower relative humidity (RH) are conducive to higher O 3 concentration and more severe air pollution. The averaged T max at these cities has a significant increasing trend of 0.28°C per decade, while RH decreases also significantly at a rate of −1.08% per decade. This may be the main reason why the summer O 3 concentration maintains stability at a high level in the recent 9 years. Results also indicate that the ‘heat dome’ effect, characterised by a persistent high pressure and warming air subsidence from the upper to lower troposphere, is reinforcing in recent years, and this is favourable for the occurrence of long‐lasting dry‐type high temperatures and the enhancement of O 3 pollution. Projections from 19 CMIP6 models show that the high pressure system will remarkably strengthen in the near, middle, and long terms under the moderate emission scenario (SSP2‐4.5). Therefore, the ‘heat dome’ effect will exacerbate the ozone pollution in the future.

Impact of Spartina alterniflora invasion and aquaculture reclamation on soil aggregate stability and carbon sequestration in Chinese coastal wetlands - Yanxun Xu; Wenjing Liu; Yule Lin; Hong Yang; Ping Yang; Guanpeng Chen; Dongyao Sun; Chuan Tong; Linhai Zhang; Wanyi Zhu; Kam W. Tang (Soil Ecology Letters, 2025)

Cumulative confidence-driven task offloading for object detection in maritime Internet of Things - Yanglong Sun; Wenqian Luo; Weijian Xu; Qiang Mei; Haixia Peng; Linhai Wei (Frontiers in Marine Science, 2025)
Maritime mobile edge computing (MMEC) technology facilitates the deployment of computationally intensive object detection tasks on Maritime Internet of Things (MIoT) devices with limited computing resources. However, the dynamic marine network and environmental interference in feature extraction adversely affect detection accuracy and cause delay. In this paper, we propose a cumulative confidence-driven joint scheduling strategy for image detection tasks in MMEC scenarios. The strategy employs lightweight and full models as the detection framework. Through an adaptive decision-making scheme for marine device image recognition, the proposed strategy accumulates results from different models within the framework to ensure quality of service (QoS). To obtain a dynamic offloading strategy that minimizes the total system cost of latency and energy consumption, the problem is divided into two subproblems, and a chemical reaction optimization algorithm is used to reduce the computational complexity. Then, a state normalization action project deep deterministic policy gradient (SNAP-DDPG) algorithm is proposed to handle environmental dynamics, achieving minimized system cost with satisfied QoS. The simulation results indicate that, compared to existing algorithms, the proposed SNAP-DDPG algorithm keeps object detection confidence, with latency reduced by 34.78%.

3D geological modeling of tunnel alignment in the complex mountainous region of Yongshan, China, based on multisource data fusion - Huaiyuan Sun; Liuyang Sheng; Yiming Dai; Xiaojun Li; Yi Rui; Linhai Lu (Engineering Geology, 2025)

Conversion of earthen aquaculture ponds to integrated mangrove-aquaculture systems significantly reduced the emissions of CH4 and N2O - Zhinan Su; Guanglong Qiu; Ping Yang; Hong Yang; Wenjing Liu; Lishan Tan; Linhai Zhang; Dongyao Sun; Jiafang Huang; Kam W. Tang (Journal of Hydrology, 2025)

Elevated N2O emissions from coastal small water bodies: Implications for greenhouse gas inventories - Lele Tang; Wenjing Liu; Hong Yang; Ping Yang; Chuan Tong; Yongxin Lin; Dongyao Sun; Wenjing Tan; Wenbo Lin; Pingping Guo; Linhai Zhang; Kam W. Tang (Journal of Hydrology, 2025)

Effects of plant invasion and land use change on soil labile organic carbon in southern China’s coastal wetlands - Lihua Wang; Wenjing Liu; Xueya Zhou; Shenglei Fu; Ping Yang; Chuan Tong; Hong Yang; Dongyao Sun; Linhai Zhang; Wanyi Zhu; Kam W. Tang (Soil Ecology Letters, 2025)

Use of biochar derived from Spartina alterniflora to reduce sediment methane (CH4) production potential during non-farming period in earthen aquaculture ponds - Ping Yang; Dongyao Sun; Wenjing Liu; Kaiyuan Liu; Hong Yang; Chuan Tong; Linhai Zhang; Yongxin Lin; Derrick Y.F. Lai; Lishan Tan; Weifeng Chen; Kam W. Tang (Environmental Pollution, 2025)

Reconstructing the late Quaternary soil erosion and dust deposition dynamics in the southern Loess Plateau: Insights from Lake Luyanghu sedimentary records - Hongfei Zhao; Xin Zhou; Linhai Yang; Hao Long; Liangqing Cheng; Yonghao Yan; Jie Zhou; Qianli Sun; Claudio O. Delang; Hongming He (Quaternary Science Reviews, 2024)

Plastic liners as a simple and effective approach to reduce CH4 and N2O emissions from aquaculture ponds - Ping Yang; Zhinan Su; Kam W. Tang; Hong Yang; Lele Tang; Linhai Zhang; Juhua Luo; Jiafang Huang; Minjie Hu; Dongyao Sun; Guanglong Qiu (Agriculture, Ecosystems & Environment, 2024)

Variable responses of mineral-bound soil organic carbon to land cover change in southern China’s coastal wetlands - Ping Yang; Guanpeng Chen; Linhai Zhang; Chuan Tong; Hong Yang; Wanyi Zhu; Dongyao Sun; Lishan Tan; Yan Hong; Kam W. Tang (CATENA, 2024)

Spatiotemporal distributions of dissolved N2O concentration, diffusive N2O flux and relevant functional genes along a coastal creek in southeastern China - Ping Yang; Yongxin Lin; Hong Yang; Chuan Tong; Linhai Zhang; Derrick Y.F. Lai; Dongyao Sun; Lishan Tan; Lele Tang; Yan Hong; Kam W. Tang (Journal of Hydrology, 2024)

Omnidirectional hybrid wave energy harvester for self-powered sensors in sea-crossing bridges - Linhai Lu; Huasheng Sun; Lei Han; Zutao Zhang; Hao Cao; Wei Wang; Xiaoping Wu; Xiaoqin Lyu (Ocean Engineering, 2023)

Rapid Detection of blaKPC in Carbapenem-Resistant Enterobacterales Based on CRISPR/Cas13a - Mingjun Liang; Bin Xiao; Lidan Chen; Xiaoyan Huang; Jinchao Li; Zhenzhan Kuang; Xinping Chen; Xiuna Huang; Zhaohui Sun; Linhai Li (Current Microbiology, 2023)
Klebsiella pneumoniae carbapenemase (KPC) is a crucial enzyme that causes carbapenem resistance in Enterobacterales , and infections by these "superbugs" are extremely challenging to treat. Therefore, there is a pressing need for a rapid and accurate KPC detection test to control the prevalence of carbapenem-resistant Enterobacterales (CREs). In this study, we established a novel method for detection of bla KPC , the gene responsible for encoding KPC, based on a recombinase polymerase amplification (RPA) and a CRISPR/Cas13a reaction coupled to fluorophore activation (termed RPA-Cas13a assay). We carefully selected a pair of optimal amplification primers for bla KPC and achieved a lower limit of detection of approximately 2.5 copies/μL by repeatedly amplifying a recombinant plasmid containing bla KPC . The RPA-Cas13a assay demonstrated a sensitivity of 96.5% and specificity of 100% when tested on 57 bla KPC -positive CRE strains, which were confirmed by DNA sequencing. Moreover, in 311 sputum samples, the theoretical antibiotic resistance characteristics of bla KPC -positive strains obtained by the RPA-Cas13a assay were highly consistent with the results of antibiotic susceptibility test ( Kappa = 0.978 > 0.81, P < 0.01). In conclusion, the RPA-Cas13a system is a simple and one-hour efficient technology for the detection of a potentially fatal antibiotic resistance gene.

A Precursory Signal of June–July Precipitation over the Yangtze River Basin: December–January Tropospheric Temperature over the Tibetan Plateau - Xiaying Zhu; Mingzhu Yang; Ge Liu; Yanju Liu; Weijing Li; Sulan Nan; Linhai Sun (Advances in Atmospheric Sciences, 2023)

Quantifying the dynamic processes of soil erosion and lake sediment deposition in the Holocene in China - Hongfei Zhao; Yunhong Lin; Jie Zhou; Qianli Sun; Linhai Yang; Claudio O. Delang; Hongming He (Quaternary Science Reviews, 2023)

Body weight, CYP2C19, and P2Y12 receptor polymorphisms relate to clopidogrel resistance in a cohort of Chinese ischemic stroke patients with aspirin intolerance - Zhiqiang Li; Wanqing Dong; Daorong Yang; Linhai Sun; Xianjun He; Huanhuan Hu; Jianping Zhang; Chunyu Wang; Yulin Li; Ming Zhao; Yu Kong; Yan Wang (European Journal of Clinical Pharmacology, 2020)

The Difference of Litter Decay, Litter- and Sediment-Associated Hydrolytic Enzymes between Brackish and Freshwater Tidal Marshes - Weifang Hu; Linhai Zhang; Derrick Y. F. Lai; Jintao Gao; Zhigao Sun; Chuan Tong; Yuehmin Chen; Congsheng Zeng (Estuaries and Coasts, 2019)

Identification of key genes relevant to the prognosis of ER-positive and ER-negative breast cancer based on a prognostic prediction system - Bin Xiao; Jianfeng Hang; Ting Lei; Yongyin He; Zhenzhan Kuang; Li Wang; Lidan Chen; Jia He; Weiyun Zhang; Yang Liao; Zhaohui Sun; Linhai Li (Molecular Biology Reports, 2019)

A skilful prediction scheme for West China autumn precipitation - Ting Wei; Wenling Song; Wenjie Dong; Zongjian Ke; Linhai Sun; Xiaohang Wen (Theoretical and Applied Climatology, 2019)